MAPPING PERSONALIZED LEARNING IN ELEMENTARY EDUCATION: A BIBLIOMETRIC STUDY - Putri Rachmadyanti; Sumarmi; Hari Wahyono; Riska Pristiani; Mujahidin Farid; Zetti Finalli (Universitas Majalengka, 2025)
This research aims to map the landscape of personalized learning in basic education through bibliometric analysis. The data used in this study was taken from the Scopus database, covering publications from 2004 to 2023. Using bibliometric analysis methods assisted by Vos Viewer, this research explores trends, publication patterns, and key topics that emerge in research related to personalized learning in elementary school level. The study results include 3 major theme clusters, namely Teachers, Schools and Learning Environment. Teachers, schools, and learning environments are three important pillars in a personalized learning approach, complementing each other to create meaningful learning experiences. The teacher acts as a key facilitator who designs learning methods according to the needs of each student. Schools provide policies, infrastructure and systemic support to support the implementation of personalized learning. The learning environment includes physical, social and technological components that encourage students to learn independently and collaboratively. Thoroughly understanding these three components is crucial for developing effective and relevant strategies in advancing personalized learning at the basic education level. Further exploration is needed on technological approaches in personalized learning, case-based research in specific schools, the role of feedback and teacher evaluation. These findings are important for understanding how learning innovations can be more effectively implemented in basic education contexts.